P020: Ultrasound-guided peripheral intravenous access in the emergency department: A randomized controlled trial comparing single and dual-operator technique. (15th May 2017) - Brick, C.; Chenkin, J.; Chang, Y.R.; Kapur, P.
Abstract : Introduction: Intravenous (IV) cannulation is a common and important procedure in the emergency department (ED). Ultrasound-guided IV (UGIV) insertion has been shown to be more effective than the blind approach for patients with difficult IV access. The optimal technique for UGIV insertion has not been determined. The objective of this study is to compare the first-attempt canulation success rate between a single-operator technique (provider holds the ultrasound probe while simultaneously placing the IV), with dual-operator technique (whereby a second provider holds the probe) in ED patients with predicted difficult access.Methods: We conducted a randomized controlled trial using a convenience sample of adult ED patients. Participating ED nurses received a one-hour UGIV training session on including didactic and practical training on simulated arms. Patients were enrolled if they met any of three criteria for difficult access: (1) history of difficult access, (2) no visible or palpable veins, or (3) two failed blind attempts. High-acuity patients or those unable to consent or comply with the procedure were excluded. Eligible patients were randomized to single or dual-operator technique and a maximum of two UGIV attempts were allowed. The primary outcome was first-attempt success rate. Additional outcomes included overall success rate, number of attempts, time to successful cannulation (needle insertion to flashback), patient pain scores, operator 'ease of use' scores, and complications 30 minutes after insertion including IV failure. Other variables collected included patient demographics, presenting complaint, indication for ultrasound use, relevant medical history, and location/depth of the target vessel. Fisher's exact test was used to compare success rates between groups.Results: Data collection was ongoing at the time of submission, but is expected to be completed by May 01, 2017.Conclusion: This is the first randomized-controlled trial comparing single and dual-operator ultrasound technique for difficult IV insertion in ED patients. The results from this study will provide evidence to guide education, and ensure best practice of UGIV insertion in the ED.